Hereditary succession in the mütevelli office: the case of the Menteşe region (1913-1920) - Bektas, Erhan (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
This article examines the institutional transformation of the m & uuml;tevelli office in the late Ottoman period, with particular emphasis on the implementation of the Appointment to Offices Regulation of 1913 (Tevcih-i Cihat Nizamnamesi) in the Mente & scedil;e region. It explores the gradual transition from inheritance practices grounded in familial continuity within family waqfs to a more formalized appointment process structured around state-supervised examinations. The study argues that the Ottoman state's efforts at centralization in the field of waqf administration did not aim to eliminate established waqf families; rather, they produced an administrative framework in which hereditary claims were re-legitimized through bureaucratic procedures and merit-based evaluation mechanisms. By analyzing the interaction between family, local networks and central regulatory mechanisms, this article offers a new perspective on the negotiated and multi-layered nature of Ottoman administrative institutionalization.
Keywords: The Appointment to Offices Regulation of 1913; m & uuml; tevelli appointment; waqf deeds; foundation management; the Ministry of Foundations; Area Studies